2022
DOI: 10.1161/hypertensionaha.121.18711
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gut Commensal That Compromises the Blood Pressure-Lowering Effect of Ester Angiotensin-Converting Enzyme Inhibitors

Abstract: Background: Despite the availability of various classes of antihypertensive medications, a large proportion of hypertensive individuals remain resistant to treatments. The reason for what contributes to low efficacy of antihypertensive medications in these individuals is elusive. The knowledge that gut microbiota is involved in pathophysiology of hypertension and drug metabolism led us to hypothesize that gut microbiota catabolize antihypertensive medications and compromised their blood pressure (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…Coadministration of Coprococcus comes (a species of the Coprococcus genus) and quinapril in SHRs led to lower antihypertensive effect of quinapril in vivo. 61 Coprococcus genus and C. comes species were also found tending to be more abundant in fecal samples collected from the Black hypertensives, compared with the White hypertensives. Interestingly, this correlates with the previous report that Black American hypertensive patients have a poor response to ACE inhibitors.…”
Section: Quinaprilmentioning
confidence: 84%
See 1 more Smart Citation
“…Coadministration of Coprococcus comes (a species of the Coprococcus genus) and quinapril in SHRs led to lower antihypertensive effect of quinapril in vivo. 61 Coprococcus genus and C. comes species were also found tending to be more abundant in fecal samples collected from the Black hypertensives, compared with the White hypertensives. Interestingly, this correlates with the previous report that Black American hypertensive patients have a poor response to ACE inhibitors.…”
Section: Quinaprilmentioning
confidence: 84%
“…Recent findings from our group provided evidence for direct hydrolysis of quinapril by gut microbiota and its resultant reduced antihypertensive effect. 61 We showed that depletion of gut microbiota by broad-spectrum antibiotics resulted in a better response (higher efficacy) to orally administered quinapril in the SHR, compared with those without antibiotics treatment. However, this difference was not found when quinapril was given intravenously, which is a way of bypassing the gut microbiota and related first-pass metabolism.…”
Section: Ace Inhibitorsmentioning
confidence: 84%
“…Firstly, Yang et al observed that treatment with antibiotics increased quinapril effectiveness to reduce BP in spontaneously hypertensive rats. 1 delivered orally, but not intravenously. 1 As a lipophilic ester prodrug, quinapril is normally absorbed in the intestine with its original form and is hydrolyzed in the liver to achieve its antihypertensive effects.…”
Section: How the Gut Microbiota May Impact Ester Ace Inhibitorsmentioning
confidence: 99%
“…Considering the number of different types of antihypertensive agents, pinpointing the effect of the gut microbiome for each agent will represent a major but important research effort. Given that each drug involves individual metabolic pathways that may interact with the gut microbiota in different manners, the works from Yang et al 1 could serve as a foundation for studying the microbiota-drug interactions in other class of antihypertensive drugs, especially for those already known to affect gut microbiome compositions, as discussed above. Untangling the complex microbiota-drug interactions may lead to novel personalized diagnostic and therapeutic approaches for hypertensive patients.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation